Inclusion of intrauterine device insertion to registered nurses' scope of clinical practice. Issue 1 (February 2019) - Fleming, Kirsteen; Cheng, Yan; Botfield, Jessica; Sousa, Mariana; Bateson, Deborah
Abstract: Background: Intrauterine devices are highly effective in preventing pregnancy; however uptake remains low in Australia. Extending provision to registered nurses with the required knowledge and skills to undertake IUD insertions may increase utilisation. Aim: This qualitative study explored the attitudes of nurses and medical officers in regards to extending nurses scope of practice to include intrauterine device insertion in the context of reproductive and sexual health care. Methods: Semi-structured interviews were conducted with ten nurses prior to, and four following, intrauterine device insertion training, and post-training surveys were completed by the six medical officers who provided mentoring and supervision during training. Thematic analysis was undertaken for interview and survey responses. Findings: Three key themes were identified: 1) perceived benefits and value, 2) perceived barriers and challenges, and 3) factors contributing to successful implementation. Nurses reported the addition of intrauterine device insertions was a positive expansion of their scope of practice, and that it would improve clients' access to this contraceptive method. All interviewees identified the usefulness of ongoing support for nurses through mentoring relationships. Medical officers were positive and supportive of the expansion of scope. Discussion and conclusion: Inclusion of intrauterine device insertions in registered nurses scope of practice appears feasible and well-received by registered nurses and medical officers, suggesting nurses are well-placed to provide intrauterine device insertions in Australia. Research into service delivery models will be useful to support national credentialing standards and promote inclusion of intrauterine device insertion to nurse scope of practice.